Legal and Health Protection for Creative Economy Actors during The Covid-19 Pandemic - Maharani, Andina Elok Puri; Gravitiani, Evi; Purwaningtyas, Niniek; Parwitasari, Tika Andarasni; Kusumo, Ayub Torry Satriyo; Hartanto, Heri; Damayanti, Kusmadewi Eka (Faculty of Law, Universitas Sebelas Maret, 2021)
This research examined Covid-19 from the perspective of legal and health protection by regional governments. Generally, regional governments are at the front line in protecting communities in this autonomy era due to their constitutional obligations. Data also shows that the creative economy actors in the micro, small, and medium business sector constitute over 90% of the workforce, necessitating their protection. This research used empirical-juridical research with an interdisciplinary approach examined the legislation and the community's reality. A Focus Group Discussion (FGD) was conducted with relevant stakeholders and creative economy business actors in Surakarta, Bandung, and Madiun cities. Furthermore, concepts of legal, health, and economic theories were reviewed to formulate a regional government policy draft regarding these business actors during the Covid-19 emergency. The results showed an existing form of legal protection regulation related to health and the economy at the national level. However, three big cities (Bandung, Madiun, and Surakarta) representing three provinces as research objects are yet to provide regional regulations concerning protection for creative economy actors, though the local government has encouraged an increase in their activities